Surgical treatment of inferior pole fractures of the patella: a systematic review - Chih‐Hsun Chang; Chien‐An Shih; Fa‐Chuan Kuan; Chih‐Kai Hong; Wei‐Ren Su; Kai‐Lan Hsu (Journal of Experimental Orthopaedics, 2023)
Abstract Purpose This study aimed to comprehensively review the existing evidence concerning surgical treatment of inferior pole fractures of the patella and to report the outcomes and complications of different fixation techniques. Method This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Searches of PubMed, Scopus, and Web of Science were conducted in March 2023. Studies were screened against predecided inclusion and exclusion criteria. The extracted data included fracture characteristics, surgical techniques, and radiographic and functional outcomes. The Methodological Index for Non‐Randomized Studies (MINORS) quality assessment tool was used to assess the eligible literature. The primary outcome was postoperative range of motion of different surgical methods, and the secondary outcomes were other clinical results and complications. Results A total of 42 studies satisfied all the inclusion criteria and were deemed suitable for review. Fourteen case–control studies and 28 case series were selected, for a total of 1382 patients with a mean age of 51.0 years (range = 11–90). The follow‐up period ranged from 6 to 300 months. The surgical techniques were categorized based on the device used as follows: (1) rigid fixation device; (2) tensile fixation device; (3) mixed device; and (4) extra‐patella device. Conclusion Regarding the outcomes following surgical treatment of inferior pole fractures of the patella, the postoperative range of motion (ROM) of each technique ranged from 120° to 135°, with the exception of that involving the patellotibial wire which had poorer outcomes. The lowest functional score was also found in those using the patellotibial wire. Complications after surgery are rare, but approximately half of the patients required additional surgery for implant removal, particularly those whose initial surgery involved rigid fixation devices. It's worth noting that bony fragment excision is no longer recommended, and the combined use of multiple surgical devices is now more common.